A trafficome-wide RNAi screen reveals deployment of early and late secretory host proteins and the entire late endo-/lysosomal vesicle fusion machinery by intracellular Salmonella - Kehl, Alexander (PLoS Pathog, 2020)
The intracellular lifestyle of Salmonella enterica is characterized by the formation of a replication-permissive membrane-bound niche, the Salmonella-containing vacuole (SCV). As a further consequence of the massive remodeling of the host cell endosomal system, intracellular Salmonella establish a unique network of various Salmonella-induced tubules (SIT). The bacterial repertoire of effector proteins required for the establishment for one type of these SIT, the Salmonella-induced filaments (SIF), is rather well-defined. However, the corresponding host cell proteins are still poorly understood. To identify host factors required for the formation of SIF, we performed a sub-genomic RNAi screen. The analyses comprised high-resolution live cell imaging to score effects on SIF induction, dynamics and morphology. The hits of our functional RNAi screen comprise: i) The late endo-/lysosomal SNARE (soluble N-ethylmaleimide-sensitive factor attachment protein receptor) complex, consisting of STX7, STX8, VTI1B, and VAMP7 or VAMP8, which is, in conjunction with RAB7 and the homotypic fusion and protein sorting (HOPS) tethering complex, a complete vesicle fusion machinery. ii) Novel interactions with the early secretory GTPases RAB1A and RAB1B, providing a potential link to coat protein complex I (COPI) vesicles and reinforcing recently identified ties to the endoplasmic reticulum. iii) New connections to the late secretory pathway and/or the recycling endosome via the GTPases RAB3A, RAB8A, and RAB8B and the SNAREs VAMP2, VAMP3, and VAMP4. iv) An unprecedented involvement of clathrin-coated structures. The resulting set of hits allowed us to characterize completely new host factor interactions, and to strengthen observations from several previous studies.